EARNINGS MANAGEMENT,COMPANY SIZE, LEVERAGE AND PROFITABILITY ON AUDIT RISK AND AUDIT REPORT LAG - Kurniawati, Arie Dwi (International Conference On Economics Business Management And Accounting (ICOEMA), 2023)
The research objective is to determine the effect of Earnings Management,Company Size, Leverage and Profitability Against Audit Risk and Audit Report Lag.The research method usesdescriptive research, namely a contextual research that makes humans as instruments and adapted to reasonable situations in relation to data collection which are generally qualitative in nature.Analysis techniqueusing the triangulation method. earnings management has a positive and negative influence on audit report lag. Profitability has no negative effect on audit report lag. company size has a positive and negative effect on audit report lag. leverage has a positive effect on audit report lag. Audit risk positively mediates the relationship between earnings management on audit report lag and on firm size and profitability. Audit risk is not able to mediate. The auditor's business risk has a positive relationship with audit report lag.